ANALISIS BERPIKIR KRITIS MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH KONTROVERSIAL [THE ANALYSIS OF STUDENTS’ MATHEMATICAL CRITICAL THINKING FOR SOLVING CONTROVERSIAL ISSUES] - Suryawan, I Putu Pasek; Ratnaya, I Gede (Universitas Pelita Harapan, 2023)
This research is a descriptive study using a qualitative approach with the aim of analyzing students' critical thinking skills in solving controversial mathematics problems using six indicators of IDEALS critical thinking. The research subjects in this study were 3 students of class X MIPA 1 SMA N 1 Singaraja who were obtained through a purposive sampling method. The research instruments this time were researchers, student worksheets, student test results, and interview results. Miles and Huberman's model is used in analyzing research data, through the process of data reduction, data presentation, and ending with drawing conclusions based on the data obtained. The results of the research and interviews show that students' critical thinking skills solve controversial mathematics problems with six indicators of IDEALS critical thinking, namely: (1) identify, it is found that the three subjects are able to identify the main problem and identify solutions to problems given that do not make sense, (2 ) define, it was found that the three subjects could define what was known and what was asked in the mathematical problem, but only by re-copying the questions, (3) enumerate, it was found that the three subjects only found one problem solving strategy that made sense, (4) analyze , each of the three subjects only used one problem-solving strategy for analysis, (5) list, it was found that the three subjects were able to state reasons for using the problem-solving strategy they used respectively, and (6) self-correct, it was obtained that the three subjects have re-checked the delivery strategy problem solutions that they use.BAHASA INDONESIA ABSTRACT: Penelitian ini merupakan penelitian deskriptif menggunakan pendekatan kualitatif dengan tujuan menganalisis kemampuan berpikir kritis siswa dalam menyelesaikan masalah kontroversial matematika menggunakan enam indikator berpikir kritis IDEALS. Subjek penelitian dalam penelitian ini yaitu 3 orang siswa kelas X MIPA 1 SMA N 1 Singaraja yang didapatkan melalui metode purposive sampling. Dengan instrumen penelitian kali ini yaitu peneliti, lembar kerja siswa, hasil tes siswa, dan hasil wawancara. Model Miles dan Huberman digunakan dalam menganalisis data penelitian, melalui proses reduksi data, penyajian data, serta diakhiri dengan penarikan kesimpulan berdasarkan data yang diperoleh. Adapun hasil penelitian serta wawancara menunjukkan bahwa kemampuan berpikir kritis siswa menyelesaikan masalah kontroversial matematika dengan enam indikator berpikir kritis IDEALS, yaitu: (1) identify, diperoleh bahwa ketiga subjek mampu mengidentifikasi pokok permasalahan dan mengidentifikasi solusi dari masalah yang diberikan tidak masuk akal, (2) define, diperoleh bahwa ketiga subjek dapat mendefinisikan terkait yang diketahui serta apa yang ditanyakan pada persoalan matematika, tetapi hanya dengan menyalin ulang soal, (3) enumerate, diperoleh bahwa ketiga subjek hanya menemukan satu strategi penyelesaian masalah yang masuk akal, (4) analyze, masing-masing dari ketiga subjek hanya menggunakan satu strategi penyelesaian masalah tersebut untuk dianalisis, (5) list, diperoleh bahwa ketiga subjek mampu menyebutkan alasan menggunakan strategi penyelesaian masalah yang mereka gunakan masing-masing, dan (6) self-correct, diperoleh bahwa ketiga subjek sudah mengecek kembali strategi penyelesaian masalah yang masing-masing mereka gunakan.